BIOLOGY AND INTRINSIC GROWTH RATE OF EARWIG (Euborellia annulata) - Nonci, Nurnina (Indonesian Journal of Agricultural Science, 2005)
Earwig (Euborellia annulata) is a potential predator of cornborer (Ostrinia furnacalis), one of the most important pests ofcorn. To include the use of predator in integrated pestmanagement (IPM) to control the pest, it is necessary tounderstand the basic information of the predator. This studyaimed to know biology and intrinsic growth rate of the predatorfeed on an artificial media (dog food). Ten pairs of newlyemerging adults of the predator were placed in a small plasticcontainer containing a mixture of soil and sand (1:1 v/v)supplemented with an artificial food. The average temperatureand relative humidity during the study were kept at 27.9-30.3oCand 76.7-92.3%, respectively. The biological aspects of thepredator evaluated were number of eggs laid, hatched, and died,as well as its oviposition period and adult mortality. Theintrinsic growth rate was studied from a group of 200 newly laideggs and results were analyzed based on the method of Birch.The biological aspects study showed that number of eggs laid bya single female of E. annulata was 86-166, which were laid fivetimes in a group of 9-45 eggs. The nymph consists of fiveinstars. Length of nymphs varied ranging from 4 to 13 mmdepends on their instar. The fifth instar nymph period was 4-6days for female and 2-3 days for male. The period of first matingwas shorter; the shortest was 2 minutes and the longest one was70 minutes. Both male and female were able to do mating severaltimes at an interval of several seconds or minutes. Pre-ovipositionperiod was 6-13 days. The eggs were deposited five times, the first,second, third, fourth, and fifth oviposition period were 7-22 days,7-21 days, 7-18 days, 11-18 days, and 11-21 days, respectively.The oviposition period was 32-59 days and postoviposition periodwas 21-51 days. Ratio between male and female was 1.4:1.0. Theaverage natural mortality of E. annulata was 10.5% which meansthat 89.5% of deposited eggs hatched became nymphs. The studyalso revealed that the intrinsic growth rate (r) of the predator was0.0772, net reproductive rate (R0) 80.16, limited growth rate (Î»)1.17, nymph stage period 39-46 days, and adult longevity of maleand female were 57-75 and 61-89 days, respectively. The studyimplies that E. annulata is potential to be incorporated in IPMfor controlling corn borer.